1982
DOI: 10.1021/jm00344a003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hypoglycemic activity of phenylalkyloxiranecarboxylic acid derivatives

Abstract: A series of new 2-(phenylalkyl)oxirane-2-carboxylic acids has been synthesized and studied for its effects on the concentration of blood glucose. Most of the compounds exhibit remarkable blood glucose lowering activities in fasted rats. Structure-activity studies reveal that substituents like Cl or CF3 on the phenyl ring and a chain length of three to five carbon atoms lead to the most effective substances. Among these compounds, ethyl 2-[5-(4-chlorophenyl)pentyl]oxirane-2-carboxylate (36) exhibits the most fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In this study, a selected potent agent of a new class of hypoglycaemic compounds [11] is shown to produce a dose-dependent decrease of glucose and ketone bodies in several normal and diabetic animals. Since B 807-27 has the same potency as its ester B 807-06, and no significant difference exists between per os and IV administration, it seems likely that the anion of B 807-27 is the active compound reaching the site of action in the target tissues.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, a selected potent agent of a new class of hypoglycaemic compounds [11] is shown to produce a dose-dependent decrease of glucose and ketone bodies in several normal and diabetic animals. Since B 807-27 has the same potency as its ester B 807-06, and no significant difference exists between per os and IV administration, it seems likely that the anion of B 807-27 is the active compound reaching the site of action in the target tissues.…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition of fatty acid oxidation is associated with reduced hyperglycemia due to inhibition of glucose production [35,40]. Most of the investigational CPT-1 inhibitors have been shown to cause hypoglycemia and some also cause hypoketonemia [121].…”
Section: Oxfenicinementioning
confidence: 99%
“…In method a, appropriate bromides were added to diethyl malonate affording diethyl monosubstituted malonate derivatives type 1, which gave the monoesters type 2 after saponification. 25 Ethyl R-substituted-acrylates 3a-e were obtained by treatment of ethyl monosubstituted malonates 2 and paraformaldehyde, under Knoevenagel reaction. Compound 3f was obtained by substitution of the acetoxy group of acrylate 4, by nucleophilic attack of the appropriate Grignard reagent, in the presence of CuI (method b).…”
Section: Chemistrymentioning
confidence: 99%